Layered nanosheet Cu4 (OH) 6FCl electrode material and preparation method and application thereof

3D porous Cu4(OH)6FCl nanosheets were synthesized by ion co-precipitation method, which solved the problem of unifying high capacity and long cycle of traditional transition metal halide electrode materials in lithium metal batteries, achieved efficient lithium storage and stable cycle, and avoided the use of toxic reagents.

CN120637436APending Publication Date: 2025-09-12NORTHEAST NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510764034.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-09
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Traditional transition metal halide electrode materials cannot achieve the combination of high capacity and long cycle time in lithium metal batteries due to their large particle size, low active site utilization, large volume expansion during the cycle, and the use of toxic reagents in the synthesis process.

Method used

Three-dimensional porous Cu4(OH)6FCl nanosheets were synthesized by ion co-precipitation method, using NH4F and CuCl2·2H2O as precursors. The 3D porous structure of Cu4(OH)6FCl nanosheets was formed by static reaction, ensuring that the redox active sites were fully exposed and providing a larger interface area.

Benefits of technology

High active material utilization was achieved, lithium storage capacity and cycle stability were significantly improved, the use of toxic reagents was avoided, and the synthesis process was simplified. The obtained Cu4(OH)6FCl electrode material exhibited high specific capacity, excellent rate performance and long cycle life in lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120637436A_ABST
    Figure CN120637436A_ABST
Patent Text Reader

Abstract

The invention discloses a layered nanosheet Cu4 (OH) 6FCl electrode material and a preparation method and application thereof.According to the layered nanosheet Cu4 (OH) 6FCl electrode material and the preparation method and application thereof, a simple and convenient ion co-deposition method is adopted, NH4F and CuCl2. 2H2O which can be easily obtained are used as precursors to be subjected to a standing reaction to synthesize a three-dimensional Cu4 (OH) 6FCl nanosheet, the 3D porous structure can ensure that redox active sites of the Cu4 (OH) 6FCl electrode material are completely exposed, and the Cu4 (OH) 6FCl electrode material can be used for preparing the three-dimensional Cu4 (OH) 6FCl nanosheet. Ion diffusion kinetics are enhanced, and effective charge storage is increased. Compared with traditional transition metal halides (CuF2 and CuCl2), the cathode of the lithium metal battery based on Cu4 (OH) 6FCl shows excellent high reversible capacity and excellent cycling stability. Meanwhile, the simple and convenient synthesis method used in the invention effectively avoids the use of toxic reagents which are harmful to the environment, saves the cost and is suitable for large-scale production. The method conforms to the development concept of environmental protection, and unification of economic benefits, social benefits and environmental benefits is comprehensively achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a layered nanosheet Cu4(OH)6FCl electrode material, a preparation method thereof, and applications thereof. Background Art

[0002] Lithium metal batteries (LMBs) have a high theoretical specific capacity (3860 mAh g -1 ) and the lowest redox potential (-3.04 V compared to standard hydrogen electrode) and are widely considered the "holy grail" of high energy density rechargeable batteries. However, commercial intercalation transition metal oxide cathodes face an inherent capacity ceiling, hindering their adoption in next-generation high energy demand applications. In pursuit of higher energy density and lithium storage capacity to meet the growing needs of modern energy storage systems, research efforts have shifted to exploring the potential of transition metal halides (TMHs) as LMB electrode materials. Compared to traditional transition metal oxides, TMHs have higher redox potentials and, when used as cathode materials in LMBs, can achieve a higher discharge platform, which is beneficial to improving energy density. In addition, compared with LiFePO4 (~170 mAh g -1 )、LiCoO2(~274mAh g -1 ) and LiNi x Co y Mn 2-x-y O2(~280mAh g -1 Compared with commercial intercalation metal oxide cathodes such as CuCl2 and CuF2, the theoretical capacity of TMHs is significantly higher (397 mAh g -1 and 528mAh g -1 ), making it a promising candidate for high-performance energy storage applications.

[0003] However, the synthesis of TMHs typically involves the use of highly corrosive and toxic reagents, such as hydrofluoric acid and hydrochloric acid, which pose significant health risks and environmental hazards. In addition, traditional TMHs are typically characterized by relatively large particle sizes (ranging from hundreds of nanometers to several micrometers), which leads to limited electrode / electrolyte interface area and extended ion diffusion pathways. These factors hinder the practical utilization of TMHs and prevent them from fully realizing their theoretical capacity potential.

[0004] Recent studies have shown that electrode materials composed of nanoscale particles can often exceed their theoretical specific capacity. Furthermore, nanoscale electrode materials exhibit improved tolerance to volume expansion during lithiation, reducing crack formation and capacity decay during cycling. Inspired by this, the development of nanoscale TMHs has emerged as a viable strategy for exploiting interfacial energy storage effects and enhancing practical capabilities. Therefore, the size effect of active materials plays a key role in determining the electrochemical performance and charge storage mechanism of batteries. Overcoming the inherent technical limitations of TMHs and achieving a balance between high capacity and long cycling life remains a major challenge for TMH materials. Summary of the Invention

[0005] The present invention aims to provide a layered nanosheet Cu4(OH)6FCl electrode material, its preparation method, and application, to address the problem that TMH materials, limited by their size, cannot achieve both high capacity and long cycling performance. This invention proposes a simple and scalable ion coprecipitation method to synthesize three-dimensional (3D) porous Cu4(OH)6FCl nanosheets using NH4F and CuCl2·2H2O as precursor materials. Compared with traditional bulk materials, the 3D porous structure of the Cu4(OH)6FCl nanosheets of the present invention ensures that redox active sites are fully exposed to the electrolyte, thereby promoting enhanced ion transport kinetics and improving utilization efficiency. In addition, the nanosheet morphology provides a larger interfacial area, thereby realizing additional ion storage capacity. Leveraging these structural advantages, LMB cathodes made from 3D porous Cu4(OH)6FCl nanosheets exhibit significant specific capacity, as well as excellent rate capability and cycling stability.

[0006] To achieve the above object, the first aspect of the present invention provides a method for preparing a Cu4(OH)6FCl electrode material, comprising the following steps:

[0007] (1) Prepare CuCl2·2H2O aqueous solution and NH4F aqueous solution;

[0008] (2) mixing a CuCl2·2H2O aqueous solution and an NH4F aqueous solution and allowing them to react;

[0009] (3) After the reaction is completed, the obtained precipitate is centrifuged and dried to obtain the Cu4(OH)6FCl electrode material.

[0010] Preferably, the static reaction conditions are: reacting at 25-50° C. for 2-10 hours.

[0011] The present invention carries out a static reaction at a specific temperature. When the temperature is below 25°C, the growth rate of Cu4(OH)6FCl nanosheets is inhibited and the obtained Cu4(OH)6FCl is very small. When the temperature is higher than 50°C, it is not conducive to the formation of Cu4(OH)6FCl nanosheets.

[0012] More preferably, the static reaction condition is: reacting at 25°C for 6 hours.

[0013] Preferably, the molar ratio of CuCl2·2H2O to NH4F is 1:1-4.

[0014] Preferably, during the mixing process, CuCl2·2H2O aqueous solution and Cu in NH4F aqueous solution 2+ , F- and Cl- ions self-assemble into Cu4(OH)6FCl, and a light blue precipitate is observed after standing reaction.

[0015] The present invention mixes a certain proportion of CuCl2·2H2O solution and NH4F solution and leaves the mixture to stand for a period of time. During this period, the CuCl2·2H2O solution in the mixture is 2+ 、F - and Cl - ions self-assemble into 3D porous Cu4(OH)6FCl nanosheets. In the Cu4(OH)6FCl sample, there are Cu 2+ Two coordination environments, Cu1 2+ Coordinated with six hydroxyl groups, Cu2 2+ Through coordination bonds with four hydroxyl groups and two Cl - ion binding. In addition, F - The ion is hydrogen bonded to the six surrounding hydroxide ions (OH - ) interactions, thereby enhancing their stability in the cavity.

[0016] Preferably, the centrifugal conditions are: centrifugation at 5000-10000 rpm for 1-10 min; and the drying conditions are: drying at 50-80° C. for 6-10 h.

[0017] More preferably, the centrifugation condition is: centrifugation at 8000 rpm for 5 min; and the drying condition is: drying at 60° C. for 8 h.

[0018] A second aspect of the present invention provides a Cu4(OH)6FCl electrode material, which is prepared by the above-mentioned preparation method.

[0019] Preferably, the Cu4(OH)6FCl electrode material is in the form of layered nanosheets, and the thickness of each layer of the nanosheet is 30 to 40 nm.

[0020] A third aspect of the present invention provides an application of a Cu4(OH)6FCl electrode material, and an application of the Cu4(OH)6FCl electrode material in a positive electrode sheet of a lithium metal battery.

[0021] Preferably, the preparation method of the lithium metal battery is:

[0022] S1: Preparation of negative electrode sheet

[0023] The metallic lithium is pressed and cut to obtain a negative electrode sheet;

[0024] S2: Preparation of electrolyte

[0025] Dissolve LiPF6 in an organic solvent to prepare a LiPF6 electrolyte with a concentration of 1 mol / L;

[0026] S3: Preparation of positive electrode

[0027] The Cu4(OH)6FCl electrode material, conductive carbon and a binder are mixed to obtain a slurry, which is then coated on a copper foil and dried to obtain a positive electrode sheet;

[0028] S4: Preparation of lithium metal batteries

[0029] The negative electrode sheet, separator, electrolyte and positive electrode sheet are assembled in sequence to obtain a lithium metal battery.

[0030] More preferably, the organic solvent consists of dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate in a volume ratio of 1:1:1.

[0031] Therefore, the present invention adopts the above-mentioned layered nanosheet Cu4(OH)6FCl electrode material and its preparation method and application, which has the following beneficial effects:

[0032] (1) The present invention successfully synthesized Cu4(OH)6FCl nanosheets using a simple, environmentally friendly and scalable strategy. Compared with traditional bulk materials such as CuF2 and CuCl2, the active site utilization rate of 3D porous Cu4(OH)6FCl nanosheets is as high as 92.7%, which significantly improves its lithium storage capacity in lithium metal batteries (LMBs). -1 When the Cu4(OH)6FCl cathode was used, the LMB exhibited a higher specific capacity (958 mAh g -1 ), which greatly exceeds CuCl2 and CuF2. In addition, Cu 2+ The strong bonding between OH- / Cl- contributes to the excellent structural stability of Cu4(OH)6FCl nanosheets. -1 When the Cu4(OH)6FCl cathode was used, it showed excellent cycling stability, and the capacity did not decrease significantly after 1000 cycles.

[0033] (2) The present invention uses NH4F and CuCl2·2H2O as raw materials to prepare the product, effectively avoiding the use of toxic reagents in the synthesis process, and the synthesis method is simple and fast.

[0034] (3) The present invention solves the problems of traditional transition metal halides, such as large size, low utilization of active sites, large volume expansion during the cycle, complex synthesis process and the need to use toxic reagents, so that the obtained Cu4(OH)6FCl electrode material achieves the unity of high capacity and long cycle life.

[0035] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Schematic diagram and characterization diagram of the synthesis of Cu4(OH)6FCl, wherein a is the schematic diagram of the synthesis of the Cu4(OH)6FCl sample in Example 1; b is the XRD characterization diagram of the Cu4(OH)6FCl sample in Example 1; c is the FTIR characterization diagram of the Cu4(OH)6FCl sample in Example 1; d is the scanning electron microscope image of the Cu4(OH)6FCl sample in Example 1; e is the transmission electron microscope image of the Cu4(OH)6FCl sample in Example 1; f is the magnified transmission electron microscope image of the Cu4(OH)6FCl sample in Example 1; gk are mapping diagrams of Cu, O, F and Cl in the Cu4(OH)6FCl sample, respectively;

[0037] Figure 2 The Cu4(OH)6FCl electrode material of Example 1 is 0.01-3V, 0.2mV s -1 The CV curves of the first four cycles are shown below;

[0038] Figure 3 The Cu4(OH)6FCl electrode material of Example 1 is subjected to a current density of 0.04Ag -1 The constant current charge and discharge curves of the first four cycles are shown below;

[0039] Figure 4 Graph showing the charge / discharge capacity of the Cu4(OH)6FCl electrode material of Example 1 at different current densities;

[0040] Figure 5 Nyquist plot of the Cu4(OH)6FCl electrode material of Example 1 at frequencies of 10 mHz-100 kHz;

[0041] Figure 6 The Cu4(OH)6FCl electrode material of Example 1 is 0.64Ag -1 Cyclic stability test diagram below;

[0042] Figure 7 1 is a capacity comparison chart of the Cu4(OH)6FCl electrode material of Example 1 and that reported in existing literature;

[0043] Figure 8 The capacitance contribution calculation diagram of the Cu4(OH)6FCl electrode material in Example 1, where a is within the voltage window of 0.01-3 V, 0.2 mV s -1 , 0.4mV s -1 , 0.6mV s -1 , 0.8mV s -1 and 1.0mV s -1 a) is the cyclic voltammetry curve of Cu4(OH)6FCl electrode material; b) is the capacitance contribution diagram of Cu4(OH)6FCl electrode material at different scan rates. DETAILED DESCRIPTION

[0044] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and specific operation process, but the present invention is not limited to this embodiment.

[0045] Example 1

[0046] The preparation method of Cu4(OH)6FCl electrode material comprises the following steps:

[0047] S1. Prepare 100 mL of 0.5 M NH4F aqueous solution and 100 mL of 0.25 M CuCl2·2H2O aqueous solution, mix the two solutions, and let them stand at 25°C for 6 h. A light blue precipitate was observed.

[0048] S2. The obtained light blue precipitate was centrifuged at 8000 rpm for 5 min, and then dried in a vacuum drying oven at a drying temperature of 60° C. for 8 h to obtain a Cu4(OH)6FCl electrode material.

[0049] Comparative Example 1

[0050] The CuCl2 electrode material is a commercial electrode material and was purchased directly.

[0051] Comparative Example 2

[0052] The preparation method of CuF2 electrode material is commercial electrode material, which is directly purchased.

[0053] Example 2

[0054] The Cu4(OH)6FCl electrode material prepared in Example 1 was characterized. The synthesis process and characterization results are shown in Figure 1 .

[0055] Figure 1a is a schematic diagram of the synthesis process of 3D porous Cu4(OH)6FCl nanosheets in Example 1. As can be seen from the figure, a solution containing 0.25M CuCl2·2H2O is mixed with another solution containing 0.5M NH4F and allowed to stand for 6 hours. During this period, the Cu in the solution 2+ , F- and Cl- ions self-assemble into 3D porous Cu4(OH)6FCl nanosheets.

[0056] Figure 1 b is the X-ray diffraction (XRD) characterization diagram of the Cu4(OH)6FCl nanosheets synthesized in Example 1. It can be seen from the figure that the prominent diffraction peaks at 2θ = 15.33°, 30.94°, 33.06°, 36.68°, 50.71°, 54.90° and 69.39° correspond to the (100), (200), (112), (202), (302), (220) and (206) planes of claringbullite-type Cu4(OH)6FCl (JCPDS29-0539), confirming the successful synthesis of Cu4(OH)6FCl nanosheets.

[0057] Figure 1 c Fourier transform infrared (FTIR) characterization of Cu4(OH)6FCl nanosheets synthesized in Example 1. The FTIR spectrum is at 3216 cm -1 The obvious stretching peak is shown at 1044 cm, which corresponds to the specific -OH in Cu4(OH)6FCl. -1 and 853cm -1 The peak at can be classified as the Cu-OH deformation mode v Cu-O-H , the above results further demonstrated the successful synthesis of Cu4(OH)6FCl nanosheets.

[0058] like Figure 1 As shown in Figure d, the Cu4(OH)6FCl sample exhibits a layered nanosheet morphology with a thickness of ∼34 nm. Figure 1 As shown in Figure e, the high-resolution TEM (HRTEM) image shows uniform lattice fringes across the entire nanosheet, indicating that the Cu4(OH)6FCl nanosheet has obvious single crystallinity. The lattice spacing of 0.57 nm is clearly visible, corresponding to the interlayer spacing associated with the characteristic peak at 2θ = 15.33°, confirming the long-range ordered crystal structure of Cu4(OH)6FCl. Figure 1 The ordered lattice structure observed in f further reflects the regular arrangement of nanosheets. Figure 1 The elemental mapping results of gk showed that Cu, F, Cl, and O were uniformly distributed on the Cu4(OH)6FCl nanosheets, confirming the successful synthesis.

[0059] Example 3

[0060] The electrochemical performance of the Cu4(OH)6FCl electrode material prepared in Example 1 was tested.

[0061] (1) Battery assembly:

[0062] Cu4(OH)6FCl electrode material (80 mg), conductive carbon (10 mg), and polymer binder (polyvinyl fluoride, PVDF) (10 mg) in a mass ratio of 8:1:1 were mixed in 5 mL of N-methylpyrrolidone to form a slurry, which was then evenly coated on a 15 μm thick Cu foil with a coating amount of 0.00021 g / cm 2 , and dried in a vacuum oven at 120 °C overnight;

[0063] The dried copper foil coated with electrode material was cut into discs with a diameter of 6 mm. In a glove box filled with argon (O2 and H2O <1 ppm), CR2025 button batteries were assembled using metal lithium foil as the counter electrode and reference electrode and 1 mol / L LiPF6 (EC:EMC:DMC=1:1:1 vol.) as the electrolyte.

[0064] The battery was electrochemically tested. When performing cyclic voltammetry scanning, the range of the cyclic voltammetry characteristic curve was set to 0.01V~3V and the scanning rate was 0.2mVs. -1 ~1mVs -1 When performing constant current charge and discharge tests, the voltage range is set to 0.01V~3V and the current intensity is 10μA~640μA. When performing impedance tests, the frequency range is set to 100kHz~10mHz and the voltage amplitude is 10mV. When performing cycle stability tests using constant current charge and discharge, the voltage range is set to 0.01V~3V and the current density is set to 0.64Ag -1 , the number of cycles is 1000 times.

[0065] (2) Test results:

[0066] The electrochemical performance of Cu4(OH)6FCl electrode material was studied by assembling a coin-type lithium metal battery with Cu4(OH)6FCl electrode material as the working electrode and lithium foil as the counter electrode and reference electrode. -1 At a scan rate of , the first four cyclic voltammetry (CV) cycles were as follows Figure 2 As shown. Figure 2 It can be seen that during the first discharge process, two different reduction peaks at 1.53 V and 0.47 V were observed, corresponding to the lithiation of Cu4(OH)6FCl and the reduction of Cu 2+ Reduction to Cu0 During the first charge, two obvious oxidation peaks appeared at 1.21V and 1.83V, and a weaker oxidation peak appeared at 2.52V. The oxidation peak at 1.21V corresponds to Cu 0 Oxidation to Cu + , and then completely oxidized to Cu at 2.52 V 2+ Starting from the second discharge process, the reduction peak shifted to 1.26 V, which was mainly due to the solid electrolyte layer produced by partial electrolyte decomposition during the initial discharge. The CV curves from the second to the fourth cycle overlapped well, indicating that the self-assembled 3D porous Cu4(OH)6FCl nanosheets have excellent structural stability.

[0067] The galvanostatic charge / discharge (GCD) curves further verified the excellent lithium storage capacity of the 3D porous Cu4(OH)6FCl nanosheet cathode. Figure 3 As shown, the first discharge and charge capacity of the Cu4(OH)6FCl cathode is 2000mAh g -1 and 1048mAh g -1 The corresponding initial Coulombic efficiency (CE) was 52.4%, and the 47.6% capacity loss was mainly attributed to the formation of the irreversible solid electrolyte layer during the first discharge. In the subsequent cycles, the discharge and charge capacity stabilized at 958 mAh g -1 and 941mAh g -1 , CE approaches ~100%, demonstrating excellent redox reversibility. The first discharge curve of the Cu4(OH)6FCl cathode shows two voltage plateaus at 1.54 V and 0.57 V, which closely correspond to the reduction peak during the first CV discharge. The stable charge-discharge capacity further demonstrates the structural stability of the 3D porous Cu4(OH)6FCl nanosheets.

[0068] like Figure 4 As shown, the Cu4(OH)6FCl electrode material has excellent rate performance and can achieve deep charge and discharge at high current density.

[0069] like Figure 5 As shown, the impedance data show that the intrinsic resistance of the Cu4(OH)6FCl electrode material is ~2.36Ω before cycling and ~2.8Ω after cycling. The lower resistance is conducive to the transmission of electrons and ions, improving the utilization rate of Cu4(OH)6FCl, and the resistance change before and after cycling is small, indicating that the structure of the Cu4(OH)6FCl electrode material is stable.

[0070] The cycling stability of Cu4(OH)6FCl electrode material was further verified by long-term charge and discharge, such as Figure 6As shown in the figure, after 1000 cycles, there is no capacity decay, showing excellent lithium storage capacity and outstanding cycle stability. During the entire cycle process, the Coulombic efficiency of the Cu4(OH)6FCl electrode material remains at a level close to 100%.

[0071] like Figure 7 As shown, compared with other fluoride-based electrode materials in the prior art, the Cu4(OH)6FCl electrode material of the present invention has excellent capacity. The references corresponding to the samples in the figure are shown in Table 1:

[0072] Table 1 References

[0073]

[0074]

[0075] Table 2 Capacity of electrode materials in comparative examples and examples

[0076]

[0077] The CV curves of the Cu4(OH)6FCl cathode were analyzed at different scan rates to fully evaluate the pseudocapacitive charge storage and diffusion processes. Figure 8 As shown in a, the CV curves of Cu4(OH)6FCl cathode at different scan rates maintain similar curves and show a broader redox peak with increasing scan rate, indicating stable electrochemical kinetics. Figure 8 As shown in b, the Cu4(OH)6FCl cathode is at 0.6 mV s -1 The capacitance contribution is about 48.9%, and the pseudocapacitance contribution is about 51.1%. The theoretical capacity of the Cu4(OH)6FCl electrode is 523 mAh g -1 , while the experimentally determined capacity is 484.8 mAh g -1 , the active material utilization is 92.7%. The high active material utilization of Cu4(OH)6FCl is attributed to the 3D porous structure, which provides more active sites for lithium storage.

[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solutions of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for preparing a Cu4(OH)6FCl electrode material, characterized in that: The following steps are involved: (1) Prepare CuCl2·2H2O aqueous solution and NH4F aqueous solution; (2) mixing a CuCl2·2H2O aqueous solution and an NH4F aqueous solution and allowing them to react; (3) After the reaction is completed, the obtained precipitate is centrifuged and dried to obtain the Cu4(OH)6FCl electrode material.

2. The method for preparing a Cu4(OH)6FCl electrode material according to claim 1, wherein: The static reaction conditions are: react at 25-50°C for 2-10 hours.

3. The method for preparing a Cu4(OH)6FCl electrode material according to claim 1, wherein: The molar ratio of CuCl2·2H2O and NH4F is 1:1-4.

4. The method for preparing a Cu4(OH)6FCl electrode material according to claim 1, wherein: During the mixing process, Cu in CuCl2·2H2O aqueous solution and NH4F aqueous solution 2+ 、F - and Cl - The ions self-assembled into Cu4(OH)6FCl, and a light blue precipitate was observed after standing for the reaction.

5. The method for preparing a Cu4(OH)6FCl electrode material according to claim 1, wherein: The centrifugal conditions are: centrifugation at 5000-10000 rpm for 1-10 minutes; the drying conditions are: drying at 50-80° C. for 6-10 hours.

6. A Cu4(OH)6FCl electrode material, characterized by: The invention is prepared by the preparation method according to any one of claims 1 to 5.

7. The Cu4(OH)6FCl electrode material according to claim 6, characterized in that: The Cu4(OH)6FCl electrode material is in the form of layered nanosheets, and the thickness of each nanosheet is 30 to 40 nm.

8. The use of a Cu4(OH)6FCl electrode material according to any one of claims 6 to 7, characterized in that: Application of Cu4(OH)6FCl electrode material in lithium metal battery positive electrode.

9. The use of a Cu4(OH)6FCl electrode material according to claim 8, characterized in that: The preparation method of lithium metal battery is as follows: S1: Preparation of negative electrode sheet The metallic lithium is pressed and cut to obtain a negative electrode sheet; S2: Preparation of electrolyte Dissolve LiPF6 in an organic solvent to prepare a LiPF6 electrolyte with a concentration of 1 mol / L; S3: Preparation of positive electrode The Cu4(OH)6FCl electrode material, conductive carbon and a binder are mixed to obtain a slurry, which is then coated on a copper foil and dried to obtain a positive electrode sheet; S4: Preparation of lithium metal batteries The negative electrode sheet, separator, electrolyte and positive electrode sheet are assembled in sequence to obtain a lithium metal battery.